PERSEPSI GENERASI MUDA TERHADAP KEGIATAN PERTANIAN DI KELURAHAN BUHA KECAMATAN MAPANGET KOTA MANADO - Carolina Sofya Werembinan; Caroline B. D. Pakasi; Lyndon R. J. Pangemanan (AGRI-SOSIOEKONOMI, 2018)
This study aims to determine the perceptions of the younger generation of agricultural activities in the Buha Sub-District of Mapanget District. This research was carried out from August 2017 to May 2018. Primary data was collected through interviews of 15 generations of young people with the help of filling out questionnaires. Secondary data was obtained from the Buha Village Office, Mapanget District. This analysis uses descriptive analysis. The results of this study indicate that the perception of the younger generation of agricultural activities in the Buha Sub-District is overall negative for agricultural activities. Viewed from internal factors include education, employment, gender and age. The higher the level of education, the wider the insight of the younger generation so that the lack of interest in the younger generation in agricultural activities is getting bigger. The younger generation who already have permanent jobs in the non-agricultural sector look down on agricultural activities because they assume that agricultural activities have a low social level. Women have a low interest in agricultural activities because they assume that agricultural activities are not suitable for women because it will damage their appearance. Respondents aged 21-30 years have a low interest in agricultural activities, in addition to reduced agricultural land. External factors include socialization, parental work status and land ownership status. The younger generation with a low level of socialization results in a lack of interest in the younger generation in agricultural activities. Parents of respondents who work in agriculture or non-agriculture do not want their children to make agricultural activities the main job. The young generation whose parents still own agricultural land is still doing agricultural activities to help their parents work on their farms.